Two-year changes in anthropometric and motor ability values as talent identification indexes in youth female soccer players - Hirose, N.; Shimada, M. (The Journal of Physical Fitness and Sports Medicine, 2016)
Background: As previously reported, body height, sprint speed, change of direction (COD) performance, and muscular power can potentially form a talent identification index for elite youth soccer players. However, to be useful as an index for talent selection, the relative abilities at any given age must remain the same over time. Purpose: The present study examined the changes of anthropometric variables and motor abilities in elite female youth soccer players over two years. Method: Height, weight, body fat, lean body mass (LBM), 40 m sprint, 10 m x 5 COD, 5-step bounding, countermovement jump, and squat jump were measured in 12- and 15- year old soccer players (N = 12, 11). Then, these parameters were remeasured after two years (at 14 and 17 years of age). Correlations and changes in the rankings between the two measurements were determined. Result: Both groups had small ranking changes in height (12- to 14-year-olds: ñ=.77, 15- to 17-year-olds: ñ=.94; p <.01), LBM (ñ=.76, ñ=.87; p <.01), 40m sprint (ñ=.80 ñ=.90; p <.01) with a statistically significant correlation between initial values and those obtained two years later. On the contrary, correlations were not strong in 5-step bounding (ñ=.48, p <.05) and 10mx5 COD (ñ=.60, p <.05) for the younger group. Conclusion: These results imply that ranking changes in the sprint speed during normal soccer practice is minimal. However, the adaptability for training muscular power and COD ability is high, especially from 13 to 15 years of age, suggesting the need for more targeted training throughout the growth phases.